A power system study of NAPOCOR's proposed Leyte-Samar power grids interconnection - Compendio, Rex D. (1988)
A complete power system study on the proposed interconnection of the NAPOCOR's Leyte and Samar Power Grids that includes the formulation of the grid's economic generation schedule is the subject of this report. A microcomputer based computer program computes the most economic generation schedule when all LGPP-I units are available and another program when only two units are available. In both cases, the dispatching of the PB-I generators would only be when the grid's minimum spinning reserve could no longer be attained. Load flow solutions pinpoints areas that experience a low voltage problem specially during peak load hours but there is no overvoltage problem in any part of the system even after a load rejection. The low voltage problem is solved by changing the tap settings of the transformers supplying the affected areas. Protective Relays settings are computed based on the results of the fault analysis that gives the fault levels of the buses. The cause of PASAR's continuous load fluctuation and the consequent fluctuation of the systems voltage and frequency originates from the commercial rectifier which has an inherent 21 second cyclic operating characteristics. The commercial rectifier will be in forward direction drawing a 31 kiloampere constant current from the system for 20 seconds and will be reversed in the next 1 second. The effect of the PASAR load fluctuation to the same is not economically possible. The system is stable for other system disturbances such as three phase faults, load rejection, motor starting and generator or plant tripping. The load shedding set up of the grid is reliable enough that in all cases simulated, appropriate feeders are shed following the tripping of one or more generators in the system.